Bolivia : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bolivia. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights Bolivia's substantial economic and social progress, boosted by the commodity boom. Growth has been strong, averaging about 5 percent since 2006, and poverty has fallen by a third. During this time, the authorities built up sizable buffers and largely dedollarized the financial system. Real GDP growth is projected at 3.7 percent in 2016, which is still relatively strong by regional standards. In the medium term, growth is expected to converge toward 3.5 percent, consistent with the new commodity price normal, amid persistent twin deficits.